PERSEPSI MAHASIWA PRODI BKI UIN SUNAN KALIJAGA TERHADAP PENERAPAN METODE CERAMAH DI MASA PEMBELAJARAN DARING - Muhammad Alpin Hascan; Nur Saidah (Tarbiyatuna Kajian Pendidikan Islam, 2022)
Since the emergence of coronavirus in various parts of the world, all activities began to be housed. Every interaction must be done online, including education. In the implementation of lectures there are certainly learning methods. Lecture method as one of the learning methods that is always applied especially in the current online learning period. The question is how it is perceived in online learning, researchers are interested in knowing the perception of students regarding the use of online lecture methods. Research takes place remotely using google form media to process data. Research is discussed by qualitative methods by utilizing literacy resources such as books, articles and other ilimiah research as data collection techniques. Furthermore, the data is reviewed, discussed and linked to relevant library studies. Based on the perception of students, the results prove that the application of lecture methods in the middle of online lectures is quite effective. Students are quite familiar with online-based lectures using lecture methods, but there are several other things and skills that teachers need to master so that the lecture method does not become boring and can give maximum results.